Tecnologia digital e educação: uma análise crítica sobre a era da infância cyber - Serrano, Giovana Trettel (Universidade Federal de São Carlos, 2023)
The present undergraduate thesis has as object of study the digital technologies related to the development and the learning of the child. Knowing that we live in a society marked by the insertion of digital technology in the daily lives of individuals, as Education professionals, it is extremely important that we turn our attention to the impacts that this habit can generate in the lives of children. For this, during the bibliographical research with a qualitative edge, we addressed relevant issues for this theme, such as the historical context of the emergence of technologies in society, children's rights, child consumerism, the damage caused by the use of digital technologies and the relationship between traditional games and technological play. Therefore, we identified that the issue is even more complex than we can imagine, as it has deeper roots than the simple act of seeing a child with a technological device in his hand. It is imperative that Education be prepared to deal with the impacts caused by the use of technological devices by children, as well as to try to reduce them through raising awareness among children and families.
Digital technology and education: a critical analysis of the era of cyber childhood.
Keywords: Criança; Child; Infância; Childhood; Brincar; Play; Tecnologia; Technology; Consumismo; Consumerism; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO